The role of input in second language acquisition / Roselind Wee (Universiti Teknologi MARA, Sarawak, 1996)
Second language acquisition can be defined as the mastering of a language that is not one's mother tongue. Input refers to the information that is fed into an information processing device, in this case, the learner's brain. The rate of second language development can be determined by the quantity and quality of input.